IDENTIFIKASI FAKTOR PENYEBAB RENDAHNYA PENGUASAAN MATERI DALAM UJIAN NASIONAL MATEMATIKA SMA/MA PROGRAM IPA TAHUN AJARAN 2009/2010 DI KABUPATEN SITUBONDO - Kholilah, Dilla; Sunardi, S; Susanto, S (KadikmA, 2012)
Abstract. Secondary data from the Center for Educational Assessment Departement of Education Shows the percentage of mastery of the material at the school level in High School/Madrasah Aliyah in Situbondo calculate the volume of material objects play in the area between the two curves when playing surround the Â axis show the percentage of mastery of less then 60%. Based on the analysis of the data obtained it can be concluded that the lack of masteri is caused by several factor that is the method of teaching, teacher relations with studens, learning media, the state of the building, the method of learning student and teachers circumtances Key Words: identification, factors, low material